ACT 18 OF 2001 THE KERALA PROTECTION OF RIVER BANKS AND REGULATION OF REMOVAL OF SAND ACT, 2001 - Government of Kerala
AN ACT to protect river banks and river beds from large scale dredging of river sand and to protect their biophysical environment system and regulate the removal of river sand and for matters connected terewith or incidental thereto